QUR'ANIC DAILY LIFE DI ERA MILLENNIAL (Resepsi Konsep Kehidupan Harmonis dan Toleran Generasi Millennial di Dusun Canggal, Kaliwungu, Semarang) - Icha Maya Sofiana (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2018)
Religion is something that is inherent in one's belief, everyone has the right to choose what religion they will follow, in the Al-Qur'an the verse al-Hujurat verse 13 also has been mentioned that diversity is something absolute and natural for all humans. In this study, the author will discuss pluralism in Canggal Hamlet, where the community is a multicultural society. Not only Islam, in Canggal Hamlet there are also other religions such as Christianity, Catholicism, Hinduism and Buddhism. What's interesting to discuss here is that they can live side by side in harmony and peace. From the research carried out, it can be concluded that in generaliser, the concept of harmonious and tolerant life in Canggal village is to assume that the difference is not always synonymous with conflict, disagreement, the assumption that the self is the most right, but rather a sense of brotherhood, putting aside selfishness, and respect each other.